Safety and Tolerance of Donor-Derived Mesenchymal Stem Cells in Pediatric Living-Donor Liver Transplantation: The MYSTEP1 Study - Steffen Hartleif; Michael Schumm; Michaela Döring; Markus Mezger; Peter Lang; Marc H. Dahlke; Joachim Riethmüller; Alfred Königsrainer; Rupert Handgretinger; Silvio Nadalin; Ekkehard Sturm (Hindawi Limited, 2017)
Background. Calcineurin inhibitors (CNI) have significantly improved patient and graft survival in pediatric liver transplantation (pLT). However, CNI toxicity leads to significant morbidity. Moreover, CNIs cannot prevent long-term allograft injury. Mesenchymal stem (stromal) cells (MSC) have potent immunomodulatory properties, which may promote allograft tolerance and ameliorate toxicity of high-dose CNI. The MYSTEP1 trial aims to investigate safety and feasibility of donor-derived MSCs in pLT. Methods/Design. 7 to 10 children undergoing living-donor pLT will be included in this open-label, prospective pilot trial. A dose of 1 × 106 MSCs/kg body weight will be given at two time points: first by intraportal infusion intraoperatively and second by intravenous infusion on postoperative day 2. In addition, participants will receive standard immunosuppressive treatment. Our primary objective is to assess the safety of intraportal and intravenous MSC infusion in pLT recipients. Our secondary objective is to evaluate efficacy of MSC treatment as measured by the individual need for immunosuppression and the incidence of biopsy-proven acute rejection. We will perform detailed immune monitoring to investigate immunomodulatory effects. Discussion. Our study will provide information on the safety of donor-derived MSCs in pediatric living-donor liver transplantation and their effect on immunomodulation and graft survival.